Intestinal perfusion studies in tropical sprue. 2. Movement of water and electrolytes. Issue 6 (June 1977) - Hellier, M D; Bhat, P; Albert, J; Baker, S J
Abstract : Jejunal absorption of sodium and water has been investigated in 10 normal Indians and 11 patients with chronic tropical sprue. Normal saline and solutions containing amino acids and dipeptides were studied. In both groups little absorption of sodium and water from normal saline was seen. Mean water and sodium absorption from the free amino acid or dipeptide solutions showed no significant difference between the groups and was similar to absorption from normal saline. These results differ from data obtained in normal English subjects where at these concentrations significant stimulation of sodium and water absorption was seen. In a proportion of subjects in both groups net secretion was observed. However, no correlation was seen between mucosal histology or luminal bacteriology and sodium or water movement. These findings in patients with chronic tropical sprue are similar to findings in normal Indians and suggest that jejunal handling of sodium and water is abnormal when compared with normal English subjects, but that the mucosa is not in a secretory phase as seen in certain other diarrhoeal states or in the acute early phase of sprue.